__________________
Just replace in value of x in the function
f(0.1) = 100* (0.1)^2 / ((0.1)^2 + 0.17) = (1)/(0.18) = 5.56
f(0.1) = 5.56
f(0.8) = 100* (0.8)^2 / ((0.8)^2 + 0.17) = (64)/(0.81)= 79.01
f(0.8) = 79.01
_______________________
derivative of a quotient
Q(x)= f(x)/g(x)
Q'(x)= (f'(x)*g(x) - f(x)*g'(x)) / (g(x) ^2)
![Q^(\prime)\mleft(x\mright)=(f^(\prime)\mleft(x\mright)\cdot g\mleft(x\mright)-f\mleft(x\mright)\cdot g^(\prime)\mleft(x\mright))/(g\mleft(x\mright)^2)](https://img.qammunity.org/2023/formulas/mathematics/college/r46ca5z85mzlu2wrlbvhr8kid0s37tazpy.png)
_____________________________
If f(x) = 100* (x^2) / (x^2 + 0.17),
f'(x)= 100 * ( 2x* (x^2 + 0.17) - 2x*x^2 ) / (x^2 + 0.17)^2
f'(x)= 100 * ( 2x^3 + 2x* 0.17 - 2x^3 ) / (x^2 + 0.17)^2
f'(x)= 100 * ( 2x* 0.17 ) / (x^2 + 0.17)^2
f'(x)= 34*x/ (x^2 + 0.17)^2
_________________________
Just replace in value of x in the function
f'(0.1)= 34*(0.1)/ (0.1^2 + 0.17)^2
f'(0.1)= 3.4/ (0.18)^2
f'(0.1)= 104.9
f'(0.8)= 34*(0.8)/ (0.8^2 + 0.17)^2
f'(0.8)= 27.2/ (0.81)^2
f'(0.8)= 41.46